Analysis of methylphenol concentration in Selangor rivers, Malaysia using solid phase extraction technique coupled with UV-Vis spectroscopy - Nur ‘Izzah Ahmad Juanda; Noorashikin Md Saleh; Nor Yuliana Yuhana; Saliza Asman; Farhanini Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2023)
Methylphenol is extensively produced from pharmaceuticals, agriculture, textiles, cosmetics, and petrochemicals industries. It is a pollutant that can adversely affect public health and the ecosystem. Following the issues raised, methylphenol extraction from Selangor rivers need to be done to avoid adverse consequences. In this study, solid phase extraction (SPE) combined with ultraviolet-visible spectroscopy (UV-Vis) detection at 271 nm was utilized to extract methylphenol from Selangor rivers. The challenges reported by applying the SPE technique was to identify the optimum conditions for extraction to guarantee effective recovery of the extracted methylphenol. Therefore, this research aimed to develop an extraction technique to extract methylphenol from Selangor rivers. In this study, 3 mL Supel Swift-HLB cartridges with bed weight of 60 mg were used as SPE cartridges. The optimum conditions for methylphenol SPE were 3 mL methanol as a conditioning solvent, 6 mL of pH 5 water sample with a contact time of 4 min with adsorbent bed was practiced during sample loading, 3 mL of acetonitrile as washing solvent, and 12 mL of acetone as the elution solvent. The concentrations of methylphenol detected at five different locations collected from Sungai Klang, Sungai Selangor, and Sungai Langat ranged from 5 to 6 mg L-1. SPE coupled with UV-Vis is an appropriate method for methylphenol extraction as it simplifies sample preparation, is time saving, and can achieve a high percentage recovery of methylphenol.